Silk peptide-hyaluronic acid based nanogels for the enhancement of the topical administration of curcumin - Niu, Jiangxiu; Yuan, Ming; Liu, Yao; Wang, Liye; Tang, Zigui; Wang, Yihan; Qi, Yueheng; Zhang, Yansong; Ya, Huiyuan; Fan, Yanli (Frontiers in Chemistry, 2022)
The present study focused on the development of Cur-loaded SOHA nanogels (Cur-SHNGs) to enhance the topical administration of Cur. The physiochemical properties of Cur-SHNGs were characterized. Results showed that the morphology of the Cur-SHNGs was spherical, the average size was 171.37 nm with a zeta potential of -13.23 mV. Skin permeation experiments were carried out using the diffusion cell systems. It was found that the skin retention of Cur-SHNGs was significantly improved since it showed the best retention value (0.66 ± 0.17 μg/cm2). In addition, the hematoxylin and eosin staining showed that the Cur-SHNGs improved transdermal drug delivery by altering the skin microstructure. Fluorescence imaging indicated that Cur-SHNGs could effectively deliver the drug to the deeper layers of the skin. Additionally, Cur-SHNGs showed significant analgesic and anti-inflammatory activity with no skin irritation. Taken together, Cur-SHNGs could be effectively used for the topical delivery of therapeutic drugs.